Anisotropy of fracture toughness in nanostructured ceramics controlled by grain boundary design. (5th January 2019) - Daniel, Rostislav; Meindlhumer, Michael; Baumegger, Walter; Todt, Juraj; Zalesak, Jakub; Ziegelwanger, Tobias; Mitterer, Christian; Keckes, Jozef
Abstract: The fracture toughness of nanostructured materials depends on anisotropic physical properties of individual microstructural features, their texture and/or topology. In this work, intentionally sculptured grain boundaries of low cohesive energy were used to form "weak" and "tough" crack propagation directions within a nanocrystalline TiN film, allowing to correlate the directional arrangement of grains and anisotropy of fracture toughness. By using a selective micromechanical testing approach, two different cracking directions were probed in a scanning electron microscope by loading microcantilever beam specimens prepared parallel and perpendicular to the stacked direction of the alternately tilted columnar grains. The fracture toughness along the sculptured grain boundaries was 30% higher due to effective multiple crack deflection at the kink planes, which was not observed along weak cleavage planes in the stacked direction. The results indicate the fundamental importance of microstructural design in the synthesis of tough nanostructured ceramics, whose anisotropic mechanical properties can be controlled effectively by incorporating dedicated microstructural features of well-defined topology, orientation and density. Graphical abstract: Highlights: Weakly bonded grain boundaries designed in a zig-zag pattern were used to enhance fracture toughness of a brittle TiN ceramic. The toughening effect originates from a multiple crack deflection at the tilted grain boundaries. The observed fracture anisotropy was identified in directional arrangement of columnar grains within the material volume. It resulted in a difference of 30% between weak and tough planes inherently formed in two in-plane directions.